E-collaboration in modern organizations initiating and managing distributed projects - Kock, Ned F., 1964- (Hershey : Information Science Reference, 2008)
"This book combines comprehensive research related to e-collaboration in modern organizations, emphasizing topics relevant to those involved in initiating and managing distributed projects. Providing authoritative content, it describes issues that have implications for distributed project management, implications surrounding the use of e-collaborative environments for distributed projects, and debate related to e-collaboration support for distributed project management"--Provided by publisher.
Ηλεκτρονικό βιβλίο
Keywords: Project management; Virtual work teams -- Management; Electronic books